Training Principals to Ensure Access to Equitable Learning Opportunities in a High-Need Rural School District - Tricia Browne-Ferrigno; Robert C. Knoeppel (Educational Considerations, 2005)
During the mid-1980s in Kentucky, a grassroots advocacy group composed of 66 property-poor school districts, seven local school boards, and 22 public school students formed, calling itself the Council for Better Education, Inc.